2002
DOI: 10.1007/s00417-002-0455-1
|View full text |Cite
|
Sign up to set email alerts
|

Myocilin mutations in a population-based sample of cases with open-angle glaucoma: the Rotterdam Study

Abstract: The prevalence of MYOC mutations (2.2%) was similar to that found in hospital-based studies. Although mutations in MYOC are rare, relatives carrying this mutation run a high risk of developing the disease. Instead of submitting all members of a family with the Asn480Lys mutation to frequent follow-up, medical care can be restricted to those carrying the mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
3
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 35 publications
1
18
3
3
Order By: Relevance
“…The frequency of this single mutation, 5%, is the highest ever observed. It compares only to that reported in patients from Western Switzerland (Mataftsi et al, 2001), and it is at least twice that reported in most other studies, including in patients from other Western European countries (Cobb et al, 2002;Hulsman et al, 2002a;Michel-Rautenstrauss et al, 2002). Of note, this mutation was not detected in African and in Asian POAG patients (Yoon et al, 1999;Kubota et al, 2000;Challa et al, 2002;Mukhopadhyay et al, 2002;Pang et al, 2002;Melki et al, 2003).…”
Section: Allelic Associations With Myoc Mutations Denote Founding Effsupporting
confidence: 61%
See 1 more Smart Citation
“…The frequency of this single mutation, 5%, is the highest ever observed. It compares only to that reported in patients from Western Switzerland (Mataftsi et al, 2001), and it is at least twice that reported in most other studies, including in patients from other Western European countries (Cobb et al, 2002;Hulsman et al, 2002a;Michel-Rautenstrauss et al, 2002). Of note, this mutation was not detected in African and in Asian POAG patients (Yoon et al, 1999;Kubota et al, 2000;Challa et al, 2002;Mukhopadhyay et al, 2002;Pang et al, 2002;Melki et al, 2003).…”
Section: Allelic Associations With Myoc Mutations Denote Founding Effsupporting
confidence: 61%
“…Therefore, this patient represented a new branch of this very large POAG pedigree. The other patient presented several discordant alleles, notably at NGA13 and D1S1165, and had therefore inherited the N480K mutation from a different ancestor (Hulsman et al, 2002a). Similarly, the patient with the I499F mutation possessed alleles that were previously associated with this mutation in two large families from Western France .…”
Section: Allelic Associations With Myoc Mutations Denote Founding Effmentioning
confidence: 95%
“…14 Interestingly, haplotype analysis with 26 flanking markers spanning 8 cM showed that Asn480Lys mutations for most Northern French and Dutch had at least 2 different origins since flanking alleles diverged, demonstrating that it was a recurrent mutation. 13,14 The initial report of mutations in MYOC in POAG cases by Stone et al 7 was followed by a series of studies reporting new causative mutations and polymorphic single nucleotide polymorphisms in individuals and families of European, African, and Asian ancestry. 10,15,16 In some cases, there are distinct ethno-geographic distributions in the prevalence for some glaucoma causative variants.…”
mentioning
confidence: 99%
“…Notably, however, no other mutations were identified, despite sequencing the olfactomedin domain of exon 3 where 85-90% of mutations cluster (Fingert et al 1999). Other studies have consistently identified mutations in 2.5-4.5% of all glaucoma probands across several different populations (Faucher et al 2002;Fingert et al 1999;Hulsman et al 2002;Mataftsi et al 2001;Stone et al 1997). This suggests that the overall frequency of MYOC mutations in unselected UK POAG patients is lower than that previously reported in several other countries.…”
Section: Discussionmentioning
confidence: 65%
“…These mutations were then found in 4.4% of 227 American POAG patients with an affected first-degree relative and 2.9% of 103 patients that were unselected for family history. Additional mutations have since been identified in other glaucoma families of diverse origin, while population-based studies have confirmed that MYOC mutations are involved in a significant proportion of all POAG cases and are not confined to those with a strong family history or juvenile onset (Adam et al 1997;Alward et al 1998;Cobb et al 2002;Faucher et al 2002;Fingert et al 1999;Hulsman et al 2002;Mataftsi et al 2001;Suzuki et al 1997). The majority of mutations are clustered in a single exon that encodes an evolutionarily conserved domain with homology to the frog olfactomedin protein (Fingert et al 1999).…”
Section: Introductionmentioning
confidence: 92%